CHANGING PERSPECTIVES ON LANGUAGE LEARNING: TOWARDS MULTILINGUALITY - Angela Scarino (University of Muhammadiyah Purwokerto, 2013)
In the development of current perspectives on language learning, there is an increasing recognition of the limits of communicative language teaching as it is practiced in particular contexts and with this an emphasis on the ‘bilingual turn’ and the development of multilinguality. This emphasis represents a shift from a monolingual view of language learning to one which recognises the relationships among the language(s) that learners bring to their learning and the language being learnt. Drawing on examples from classroom based research and with recent work on development of a national curriculum for language learning in Australia, I discuss some of the characteristic features of learning within a multilingual and multicultural perspective and I discuss implications for teaching practice.